Factors Affecting The Learning Process In Extension In Kepahiang District - Timbul Rasoki; Lina Asnamawati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Indonesia's coffee consumption over the last five years has shown an increase that is consistent with the current average estimate of coffee consumption per capita in Indonesia at around 1.11 kg/capita/year. Exports in the form of beans (green beans and roasts) decreased, on the other hand exports in the form of powder, instant coffee, and coffee drinks continued to increase, except for instant coffee in 2019 which suddenly declined. The stock of coffee beans in Indonesia in the last 5 years has decreased. Coffee imports by Indonesia over the last 5 years have continued to increase, except in the form of roasted beans which have decreased slightly. The stock of coffee beans in Indonesia for the last 5 years has continued to decline. Seeing this phenomenon, researchers are interested in factors that influence the learning process in counseling in Kepahyang Regency. Determination of respondents using the method of arikunto 10% of the total population, then obtained as many as 496 respondents who will be selected randomly. Analysis of research data using path equations, while data processing uses AMOS 22 software. The results show that the variables that have a significant influence on farmers' perceptions of the learning process in extension are; X2 (Farming experience), X4 (Farmers' participation in community institutions), X5 (Access to information), X7 (Farmers' perceptions of government policies). Keywords; Factors, Learning, Counseling, Coffee Farmers